A systematic exploration of scoping and mapping literature reviews - Christou, Eirini; Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2024)
Systematic literature mapping can help researchers identify gaps in the research and provide a comprehensive overview of the available evidence. Despite the importance and benefits of conducting systematic scoping and mapping reviews, many researchers may not be familiar with the methods and best practices for conducting these types of reviews. This paper aims to address this gap by providing a step-by-step guide to conducting a systematic scoping or mapping review, drawing on examples from different fields. This study adopts a systematic literature review approach aiming to identify and present the steps of conducting scoping and mapping literature reviews and serves as a guide on conducting scoping or mapping systematic literature reviews. A number of 90 studies were included in this study. The findings describe the steps to follow when conducting scoping and mapping reviews and suggest the integration of the card sorting method as part of the process. The proposed steps for undertaking scoping and mapping reviews presented in this manuscript, highlight the importance of following a rigorous approach for conducting scoping or mapping reviews.
Keywords: Scoping review; Mapping review; Review methodology; Systematic literature mapping; Card sorting